2021
DOI: 10.48550/arxiv.2111.14741
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Domain Adaptation of Networks for Camera Pose Estimation: Learning Camera Pose Estimation Without Pose Labels

Abstract: One of the key criticisms of deep learning is that large amounts of expensive and difficult-to-acquire training data are required in order to train models with high performance and good generalization capabilities. Focusing on the task of monocular camera pose estimation via scene coordinate regression (SCR), we describe a novel method, Domain Adaptation of Networks for Camera pose Estimation (DANCE), which enables the training of models without access to any labels on the target task. DANCE requires unlabeled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Firstly, the reverse domain adaptation, i.e. the conversion of real images to synthetic has been explored for camera pose estimation, but using 'textured' 3D models derived from SfM (Yang et al, 2021a;Langerman et al, 2021;Yang et al, 2021b;Shoman et al, 2020). Therefore, the synthetic images used in those experiments, contain texture from the real world.…”
Section: Limitations Of Existing Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, the reverse domain adaptation, i.e. the conversion of real images to synthetic has been explored for camera pose estimation, but using 'textured' 3D models derived from SfM (Yang et al, 2021a;Langerman et al, 2021;Yang et al, 2021b;Shoman et al, 2020). Therefore, the synthetic images used in those experiments, contain texture from the real world.…”
Section: Limitations Of Existing Methodsmentioning
confidence: 99%
“…CycleGAN was utilised for increasing the number of synthetic images using a 3D textured model. Langerman et al (2021) propose the use of Contrastive Unpaired Translation (CUT) for performing unpaired image-image translation of synthetic images that are generated from coloured point clouds of the scene, and report their approach's performance is comparable with existing fully supervised techniques. Some works have reported that the real-synthetic strategy resulted in better performance for camera pose estimation.…”
Section: Camera Pose Estimation Using Textured 3d Modelsmentioning
confidence: 99%
“…Research in this field can be divided into direct estimation [24][25][26][27][28][29] and indirect estimation [30][31][32][33][34]. According to the supervision strategy, it can also be divided into fully supervised [24][25][26][27][28][30][31][32][33][34], semi-supervised [35,36], and unsupervised [37,38] directions. In the unsupervised direction, some emerging topics focus on few-shot learning [39], multi-modal learning [40], and virtual-real domain adaptation [41,42], etc.…”
Section: Appearance Quality Assurance Of Complex Productmentioning
confidence: 99%
“…As expressed in (10), it is also reasonable that the semantics of different patterns in the corresponding network layers should be similar. The domain adaptation performs the distribution alignment of a given pattern to the target pattern in the semantic space through technologies such as GAN [38]. This research can be seen as an extension of the former, targeting to replace manual embedding rules through end-to-end learning.…”
Section: Multi-granularity Pattern Alignmentmentioning
confidence: 99%